The Kazakhstan-European Union partnership: Modernization of the republic's financial system - Jarosław Marczak; Natalya Uvarova (DANUBE: Law, Economics and Social Issues Review, 2016)
This study examines the issue of the modernization of the Kazakh financial system considering the new, Enhanced Partnership and Cooperation Agreement with the European Union (EU) (January 19, 2015) and the Kazakh State program "Path to Europe, 2009-2011". It describes new opportunities for the establishment of a long-term partnership and cooperation between Kazakhstan and the EU for the restructuring of Kazakhstan's financial system and its convergence with international standards and European regulations. Specifically, this study covers the financial policy and the objectives of the Republic's financial sector management; legislation regulating the financing activity of business entities, particularly its transparency and accessibility to foreign investors; contradictions between the legal framework of the state on financial relations and international standards, European directives, conventions, and recommendations; and the security of financing activities of European companies. This study employs general scientific methods (theoretical analysis and generalization, comparative legal, logical, etc.) and the functional approach.
Keywords: 330; Finance; Financial System; International Standards and EU Directives; Financial Policy; Management; Financial Crisis; Regulation